FORMATION OF THE PERSONNEL DISTRIBUTION SYSTEM DURING THE FORMATION OF THE PARTY-STATE NOMENCLATURE IN THE 1920S-1930s: ON THE MATERIALS OF THE NORTH CAUCASUS - E. Tufanov (Гуманитарные и юридические исследования, 2021)
The article studies the problem of forming the system of distribution of personnel potential of the party and state nomenclature, which is relevant for history studies. The article considers the process of developing the system of distribution of party and state apparatus representatives on the basis of the analysis of decisions taken at party congresses and conferences. In addition, through the analysis of archival documents introduced for the irst time in scientific circulation, the issue of distribution of employees of the administration of the North Caucasus region at the expense of nominees for leadership of representatives of the local ethnic group is traced. In order to strengthen its position in the national regions, the Central government tried to involve representatives of the local population in the public administration of the national areas. The sources allowed the author to reveal that the centralized nature of the personnel distribution mechanism. The Central government, through the system of personnel distribution, placed its personnel potential in leading positions in the party and Soviet institutions in the center and in the regions, ensured the implementation of the party's policy in Soviet society. The functions of the party apparatus in the ield of personnel distribution were the backbone element of the party-state model of the Soviet state.